Paediatric ENT- Upper respiratory tract disorder - Asha'ari, Zamzil Amin (2015)
Upper respiratory tract disorders consist of a wide and multidisciplinary managed areas of medicine. Over 30% of the bulk of primary care medicine are related to upper airway disorders. In this presentation, the author briefly revises the anatomy of the paediatric upper airway that makes them more challenging to manage during distressed airway. A clinical approach to management of acute paediatric upper airway disorders are discuss in the majority of the slides.